The railway children - Nesbit , Edith (Lahore : Maqbool books, 2019)
The Railway Children by Edith Nesbit is a classic children's novel that follows the adventures of three siblings: Roberta (Bobbie), Peter, and Phyllis, who are forced to move from their comfortable London home to the countryside after their father is wrongfully imprisoned. The family relocates to a small house near a railway station, and the children become friends with the people around them, including the stationmaster, his daughter, and the Old Gentleman, a mysterious figure who plays a key role later in the story. The children spend their days exploring the area, often helping others in need. As the story unfolds, the children uncover the truth about their father's imprisonment and, through their actions, help to bring about his release. Their loyalty, bravery, and kindness towards others are central themes of the novel. The book is a heartwarming tale of adventure, friendship, and family, showcasing the children's growth and their positive impact on the people they meet.
Keywords: English - Novel Book; English fiction book